4-H School Enrichment: A Guide for 4-H Faculty and Staff - Andrew Toelle (EDIS, 2023)
4-H School Enrichment can give youth and parents a picture of the benefits of a longer commitment to 4-H. The purpose of this revised 8-page publication is to support 4-H agents as they plan, develop, and evaluate school enrichment programs. Written by Andrew Toelle. https://edis.ifas.ufl.edu/4h324